Improving pre-operative binary grading: relevance of p53 and PR expression in grade 2 endometrioid endometrial carcinoma - Meijs-Hermanns, Puk; Werner, Henrica M J; Kooreman, Loes; Bretová, Petra; Weinberger, Vit; Vrede, Stephanie; Alcala, Luthy S M; Amant, Frédéric; Asberger, Jasmin; Bednaříková, Markéta; Boll, Dorry; Bronkhorst, Carolien M; et al. (International journal of gynecological cancer, 2025)
OBJECTIVE: This study aimed to evaluate the association between pre-operative progesterone receptor (PR) and p53 expression and prognosis in pre-operative grade 2 endometrioid endometrial carcinoma compared with grade 1 and grade 3 carcinomas. METHODS: Three European endometrial carcinoma cohort studies were included. Patients with pre-operative grade 2 endometrioid carcinoma and known pre-operative PR and p53 status were included (n = 400), as were patients with pre-operative grade 1 (n = 602) or grade 3 (n = 148) endometrioid carcinomas. Kaplan-Meier and Cox regression analyses were performed to analyze disease-specific and disease-free survival. RESULTS: Patients with pre-operative grade 2 endometrial carcinoma and wild-type p53 plus PR-positive expression showed a similar 7-year disease-specific survival to grade 1 endometrial carcinoma patients (95.8% vs 97.5%, p = .13), while the 7-year disease-specific survival of patients with grade 2 endometrial carcinoma with p53 aberrant and/or negative PR expression (83.5%) was significantly lower (p < .001). The combination of these markers was an independent prognostic factor in multivariate Cox regression analyses. CONCLUSIONS: The prognostic impact of pre-operative p53 and PR expression in patients with grade 2 endometrioid endometrial carcinoma supports a modified binary grading system in which grade 2 patients should be pre-operatively classified as low- or high-grade depending on p53 and PR expression.
Keywords: nádory endometria; dospělí; Tumor Suppressor Protein p53; Female; Adult; ženské pohlaví; lidé; Neoplasm Grading; Receptors, Progesterone; receptory progesteronu; Aged, 80 and over; prognóza; kohortové studie; Cohort Studies; stupeň nádoru; endometroidní karcinom; nádorové biomarkery; Aged; nádorový supresorový protein p53; Prognosis; Carcinoma, Endometrioid; Biomarkers, Tumor; lidé středního věku; Endometrial Neoplasms; senioři nad 80 let; senioři; Middle Aged; Humans